Health- related Knowledge and Nursing Practice in Caring for Thai Muslim Patients with Diabetes - Prasert, Anong; Chansawang, Wannee; Petchruschatachart, Usanee (Journal of Health Science of Thailand, 2018)
The purposes of this study were to describe the health-related knowledge and nursing practice in caring for Thai Muslim patients with diabetes. A group of 102 out of a total of 104 Buddhist nurses who were working at diabetic clinics in the hospitals in Narathiwat, Pattani and Yala provinces were included. Data were collected using a questionnaire covering the health-related knowledge (r = 0.75) and nursing practice (r=0.94) in caring for Thai Muslim patients with diabetes. Data were analyzed using frequency, percentage, mean and standard deviation. The results showed that the mean scores of total nurses’ knowledge in caring for Muslim patients with diabetes (μ 0.86, σ 0.06) and all subtotal scores (stress management : μ 0.95, σ 0.07; dietary control: μ 0.90, σ 0.80; medication management: μ 0.83, σ 0.12; exercise: μ 0.74, σ 0.18); were at a high level. The mean scores of total nurses’ practice in caring for Muslim patients with diabetes (μ 3.91, σ 0.51) and subtotal scores of 3 dimensions, for example, dietary control (μ 4.22, σ 0.38), medication management (μ 3.94, σ 0.61) and exercise (μ 3.79, σ 0.67), were at a high level. Only the dimension of stress management was at a moderate level (μ 3.60, σ 0.51). Strategies to support nurses in caring for stress management of the Muslim patients with diabetes should be implemented, particularly in raising the nurses’ awareness and promoting the culturally congruent care for the Muslim population.